Un réseau sociopédagogique pour une formation en français langue étrangère (FLE) : - Jean-François Grassin (Centre National d'Enseignement à Distance, 2016)
This contribution focuses on elements of a doctoral research that was dedicated to observe the teaching / learning on a social network devoted to a university course in French as a foreign language and questions the assumption that the digital and the Internet extend the space and time to the benefit of learning. We are looking to see whether this expansion of space-time generates new opportunities to act and learn by creating such new time frames for learning. We question the individual or collective chronotopes of participation, that is to say, the typical spatio-temporal patterns of activity in the socio-educational network, as well as the schemes of attention to the socio-educational system network, observing the participation and analyzing the speech of teachers and students on their online activity.Our study shows that the new temporalities of social media remain at the margin of educational uses, because chronotopes of social activity remain implicit or come into conflict with the more conventional chronotopes of academic institutions.